New Student Admissions Management in Private Vocational Schools - Akmal Lu’lu’ Zahrota Firdaus; Bambang Sudarsono; Suyatno Suyatno (Bulletin of Pedagogical Research, 2025)
Management of New Student Admissions (PPDB) is a crucial element in ensuring that schools can provide optimal educational services. In this context, information technology plays a significant role in introducing schools through various platforms, including websites and social media, to disseminate information about the PPDB process and the flagship programs offered. This study aims to analyze the management of PPDB at SMK Muhammadiyah Petanahan, Kebumen Regency, using a qualitative descriptive approach. Data were collected through interviews with stakeholders involved in PPDB (the Principal, PPDB Chairperson, and students), observations of PPDB activities in the field, and documentation studies of promotional archives and new student admission data. The data were analyzed using Miles & Huberman's data analysis technique. The results of the study indicate that SMK Muhammadiyah Petanahan has a good reputation and several flagship programs. However, there are weaknesses in promotion that have not been maximized, especially in the use of social media. The school also faces threats from competition with other schools and societal stigma against vocational schools. Nonetheless, there are significant opportunities, including government support for vocational education and the potential for collaboration with companies for student internships. This study concludes that effective PPDB management at SMK Muhammadiyah Petanahan requires strengthening promotion through information technology, utilizing collaboration opportunities with industries, and improving facilities to address increasingly intense competition.